PEMANFAATAN MATERIAL PLASTIK HDPE BEKAS DRUM KEMASAN SEBAGAI KULIT LAMBUNG PERAHU - Amiruddin, Wilma; Hadi, Eko Sasmito; Kiryanto, Kiryanto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2014)
The use of HDPE plastic as a result of packaging chemicals as subtitution for  wooden shell of  a boat hull provides several advantages both technically and economically. Stock plastic material is relatively abundant, its price is relatively cheap, and long service life. The method used in the manufacture of HDPE plastic boat, include the preparation of materials and processing, assembly, and last is the finishing. Planning and manufacturing procedures governed by criteria which refers to the Basic Ship Theory. The end result after the ship was completed providing technical advantages in the form of increase in load capacity for boats of the same size with a wooden boat, of ± 55%, better stability, B / T> 2, the estimated lifespan of over 10 years in the boat, the process of making relatively quickly and easily. These advantages can increase productivity boat craftsman, an increase in profits of up to ± 56 % of the total profit per month